Analisa Faktor-Faktor Yang Mempengaruhi Kualitas Audit - Elen, Trismayarni; Prasetio, Mochammad Adam; Dewi, Kurnia Sari (Program Studi Akuntansi FPEB UPI, 2021)
The objective of study is to analyze effect of organizational culture, the auditor's professional code of ethics and audit fees on audit quality. The research sample are 100 respondents who were auditors from several public accounting firms located in the South Jakarta area. Multiple regression was used to test hypothesis to analyze effect of factors that cause audit quality. The results of this study shows thatÂ there has a positive effect on organizational culture, the auditor's professional code of ethics and audit fees on audit quality.